402 Treatment patterns post PARP inhibitor in epithelial ovarian cancer patients: results from an Australian, retrospective, multi-institute cohort study. (13th November 2020) - Sivakumaran, T; Krasovitsky, M; Freimund, A; Chen Lee, K; Webber, K; So, J; Norris, C; Friedlander, M; Mileshkin, L; Au-Yeung, G
Abstract : Introduction: PARP inhibitors (PARPi) have changed the management landscape for patients with epithelial ovarian cancer (EOC). However, as with many targeted therapies, treatment resistance is common. The response to treatment post-PARPi has not been well described in trials. Data is needed to better understand disease course, and guide treatment decisions. The primary aim is to describe the treatment patterns post-PARPi. Secondary aims are to describe patient characteristics who received chemotherapy post-PARPi and DoR to chemotherapy. Methods: Retrospective analysis of women with EOC treated with PARPi either in the maintenance or treatment setting and via government-funded or clinical trial access at six gynaecological oncology centres. Between 2007–2019 eligible women were identified via clinics, trial databases and pharmacy dispensing logs. Information regarding clinico-pathological characteristics and treatment outcomes were collated from medical records. Results: Eighty-five women with EOC were identified. 90.6% received chemotherapy post-PARPi, with 72.7% receiving platinum-based chemotherapy. Clinicopathological characteristics in table 1 . Best responses observed were 5.2% CR, 19.5% PR, 19.5% SD, and 55.8% PD. Median DOR was 7.0 months (range, 0.2 – 20.4 months) in 77 patients receiving chemotherapy post-PARPi. Eight patients did not receive further systemic therapy due to poor performance status. Women who received platinum doublet chemotherapy post-PARPi had a longer mPFS than those receiving platinum single agent or non-platinum chemotherapy (9.1 months vs 3.3 months vs 5.0 months, respectively p=0.0004). Conclusion: Most patients received-platinum based chemotherapy post-PARPi with a modest response rate. Potential overlapping mechanisms of resistance to PARPi and platinum require further study to improve patient outcomes.